ANALISIS PEMANFAATAN SISTEM APLIKASI DARI SEGI PENERIMAAN USER: TECHNOLOGY ACCEPTANCE BASED MODEL - Evi Yuliatun Ningsih; Ginta Ginting; Andriyansah Andriyansah (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
The use of System Application Products at PT Asuransi XYZ is more intense in the Corporate Business Department. This research was conducted to measure the level of satisfaction of SAP users and to see the actual use and use at PT Asuransi XYZ, by combining the implementation of the information system with the UTAUT model and the DeLone-McLean model. This study uses a questionnaire method with the research sample being employees who work using SAP in the Commercial Business section at PT Asuransi XYZ with a total of 72 respondents. Where the data collected is then analyzed by the Structural Equation Model method which is processed by the SmartPLS 3.0 software. The results of this study indicate that the level of satisfaction of using SAP at PT Asuransi XYZ is determined by the quality of information and work expectations. user goals may impact SAP's reuse intentions. Likewise, the intention to use can have an impact on the actual use of SAP